2002
DOI: 10.1002/cncr.10767
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of growth and radiochemosensitivity of human malignant glioma cells by acidosis

Abstract: BACKGROUNDGlioblastoma commonly is characterized by hypoxia and acidosis and the histologic features of tissue necrosis and neovascularization. Current approaches of adjuvant radiochemotherapy for patients with glioblastoma have only a modest impact on the natural course of this disease.METHODSThe authors examined the effects of acidosis on growth and response to irradiation and chemotherapy in cultured human malignant glioma cells.RESULTSThe authors found that mild acidosis (pH 7.0) inhibited the growth of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 11 publications
2
59
0
1
Order By: Relevance
“…Under tumor microenvironmental stresses, the defect in the p53 tumor suppressor protein is a critical factor for apoptosis resistance and cancer cell survival (Soengas et al, 1999). However, low pH stress inhibits cell growth in a p53-independent manner, suggesting the involvement of other mechanisms (Reichert et al, 2002). Our results suggest that enhanced cell survival by ACSL5 under low pH conditions could have a function in the progression of cancer.…”
Section: Discussionmentioning
confidence: 75%
“…Under tumor microenvironmental stresses, the defect in the p53 tumor suppressor protein is a critical factor for apoptosis resistance and cancer cell survival (Soengas et al, 1999). However, low pH stress inhibits cell growth in a p53-independent manner, suggesting the involvement of other mechanisms (Reichert et al, 2002). Our results suggest that enhanced cell survival by ACSL5 under low pH conditions could have a function in the progression of cancer.…”
Section: Discussionmentioning
confidence: 75%
“…Acidic pH-An acidic pH environment is known to delay cell growth and increase spontaneous apoptosis in cell lines derived from colon cancer and malignant glioma (45,46). However, human melanoma cells are known to survive during acidic stress (41,47).…”
Section: Human Melanoma Cells Survive and Proliferate Also At Verymentioning
confidence: 99%
“…Acidic pH-mediated induction of apoptosis was suggested to be a consequence of caspase activity (Park et al 1999). Acidic environment could modulate growth as well as radiochemosensitivity of glioma cells (Reichert et al 2002) and was demonstrated to have immunomodulatory activity by promoting the expression of IL-8 in cervical cancer cells (Xu and Fidler 2000). Hypoxia and acidity represent two factors that might be exploited therapeutically to destroy such cells.…”
Section: Introductionmentioning
confidence: 99%